PENERAPAN PERMAINAN LOMPAT CERIA UNTUK MENINGKATKAN FISIK MOTORIK ANAK USIA DINI: THE APPLICATION OF LOMPAT CERIA GAME TO IMPROVE THE PHYSICAL AND MOTOR SKILLS OF EARLY CHILDHOOD - Sakti, Syahria; Setyaningsih, Fitriani (Universitas Islam Malang, 2024)
This study aims to evaluate the impact of implementing the Lompat Ceria game in improving early childhood physical motor development. The research method is classroom action research that follows the Kemmis and Taggart model. The study included 2 cycles, where each cycle included 4 stages, namely planning, acting, observing and reflecting. Data was collected through student observations, interviews with teachers, and documentation. The results showed that some students experienced challenges in gross motor physical development, but the majority showed active engagement in the games. Nonetheless, there were variations in the level of skills demonstrated by the students. To address these challenges, the school implemented additional learning sessions before class learning began. This study makes an important contribution to the understanding of the role of the Lompat Ceria game in early childhood physical motor development. This is evidenced by the results of the average percentage of scores in each cycle increasing, namely in cycle I by 46%; cycle II by 82%. When compared to cycle I, in cycle II experienced a lot of increase of 82%, this criterion has reached more than the expected This research concludes that the cheerful jumping game method can improve children's physical motor development.